Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.26418/skjpi.v2i1.54119
|View full text |Cite
|
Sign up to set email alerts
|

Implementasi Model Project Based Learning Dalam Rangka Meningkatkan Kemampuan Berpikir Kreatif

Abstract: ABSTRAKPenelitian ini dilakukan di SMPN 4 Tarogong Kidul Garut. Hasil studi pendahuluan menunjukan bahwa berfikir kreatif SMPN 4 Tarogong kidul Garut belum optimal, di duga karena model pembelajaran project based learning yang belum optimal. Berangkat dari fenomena diatas, penelitian ini bertujuan untuk mengetahui apakah ada pengaruh model project based learning terhadap kemampuan berpikir kreatif di SMPN 4 Tarogong Kidul Garut. Metode penelitian yang digunakan adalah metode kuantitatif, dengan design peneliti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 0 publications
0
2
0
1
Order By: Relevance
“…Research conducted (Hadi and Ramadhana 2022) also obtained results, namely the increase in the average score of students who have HOTS abilities after implementing PjBL in the learning process is in the very category. The PjBL model can also improve students' creative thinking skills, this is evidenced by the research conducted by (Mulyana et al 2022) which leads to the conclusion that there are differences in students' creative thinking abilities before and after treatment, in this case the implementation of the Project Based Learning (PjBL) model. Based on several studies that have been carried out by previous researchers, it can be concluded that the PjBL method is very important and capable of improving students' HOTS abilities needed in everyday life so that PjBL learning methods can be developed by the expected skills.…”
Section: Delivering Project Resultsmentioning
confidence: 94%
“…Research conducted (Hadi and Ramadhana 2022) also obtained results, namely the increase in the average score of students who have HOTS abilities after implementing PjBL in the learning process is in the very category. The PjBL model can also improve students' creative thinking skills, this is evidenced by the research conducted by (Mulyana et al 2022) which leads to the conclusion that there are differences in students' creative thinking abilities before and after treatment, in this case the implementation of the Project Based Learning (PjBL) model. Based on several studies that have been carried out by previous researchers, it can be concluded that the PjBL method is very important and capable of improving students' HOTS abilities needed in everyday life so that PjBL learning methods can be developed by the expected skills.…”
Section: Delivering Project Resultsmentioning
confidence: 94%
“…The experimental approach is a research approach carried out by experiment, which is a quantitative research method, used to determine the effect of the independent variable (treatment) on the dependent variable (outcome) under controlled conditions. Conditions are controlled so that no other variables (apart from the treatment variable) influence the dependent variable (Mulyana et al 2022).…”
Section: Methodsmentioning
confidence: 99%
“…Pendidikan bertujuan dalam mengembangkan potensi yang dimiliki siswa, sehingga diharapkan bangsa ini mampu mengikuti perkembangan pada bidang yang bukan hanya sains, namun juga teknologi yang berkembang di abad 21. Tuntutan abad 21 mengarahkan terjadinya perubahan reorientasi pada pelaksanaan pembelajaran, meliputi pergeseran paradigma sebuah pembelajaran yang awalnya menjadikan guru sebagai pusat pembelajaran kemudian mengalami perubahan pembelajaran yang berpusat kepada siswa, pergeseran dari proses belajar yang hanya menghafal suatu konsep mengalami perubahan menjadi belajar menemukan dan membangun konsep secara mandiri yang terbukti mampu meningkatkan keterampilan berpikir kritis dan secara terampil dalam memecahkan masalah, serta pergeseran dari belajar secara individual klasik menuju pembelajaran dalam kelompok kooperatif (Mulyana et al, 2022).…”
Section: Pendahuluanunclassified